1998
DOI: 10.1104/pp.117.2.407
|View full text |Cite
|
Sign up to set email alerts
|

An Arabidopsis VPS45p Homolog Implicated in Protein Transport to the Vacuole1

Abstract: The Sec1p family of proteins is required for vesicle-mediated protein trafficking between various organelles of the endomembrane system. This family includes Vps45p, which is required for transport to the vacuole in yeast (Saccharomyces cerevisiae). We have isolated a cDNA encoding a VPS45 homolog from Arabidopsis thaliana (AtVPS45). The cDNA is able to complement both the temperature-sensitive growth defect and the vacuolar-targeting defect of a yeast vps45 mutant, indicating that the two proteins are functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
51
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 35 publications
4
51
0
Order By: Relevance
“…As observed for POK, most of these genes have been shown to be ubiquitously expressed, but to higher levels in roots (Ahmed et al, 1997;Conceic xão et al, 1997;Bassham and Raikhel, 1998;Rojo et al, 2003). Although many genes homologous to those involved in the yeast Golgi vesicle trafficking have already been identified in Arabidopsis (e.g.…”
Section: Pok Shows Significant Homology With Vps52pmentioning
confidence: 99%
See 1 more Smart Citation
“…As observed for POK, most of these genes have been shown to be ubiquitously expressed, but to higher levels in roots (Ahmed et al, 1997;Conceic xão et al, 1997;Bassham and Raikhel, 1998;Rojo et al, 2003). Although many genes homologous to those involved in the yeast Golgi vesicle trafficking have already been identified in Arabidopsis (e.g.…”
Section: Pok Shows Significant Homology With Vps52pmentioning
confidence: 99%
“…Although many homologs of these proteins have been identified in plants (e.g. Ahmed et al, 1997; Conceic xão et al, 1997;Bassham and Raikhel, 1998;Sanderfoot et al, 1998;Zheng et al, 1999) Article, publication date, and citation information can be found at www.plantphysiol.org/cgi …”
mentioning
confidence: 99%
“…In yeast, this protein functions in two transport pathways to the vacuole: (a) the carboxypeptidase Y pathway, where it is involved in fusion of TGN-derived vesicles at the PVC and interacts with the prevacuolar t-SNARE Pep12p; and (b) the cytoplasm-to-vacuole pathway, where it is required for the formation of transport intermediates at the TGN and interacts with the TGN t-SNARE Tlg2p. An Arabidopsis cDNA encoding a protein (AtVPS45) with extensive sequence similarity to yeast Vps45p is able to complement the carboxypeptidase Y sorting defects and the temperature-sensitive growth defect of a yeast vps45 mutant (Bassham and Raikhel, 1998). However, AtVPS45 in Arabidopsis resides exclusively on the TGN, not on the PVC, and interacts only with the TGN t-SNAREs and not with t-SNAREs found on the PVC (D.C. Bassham, A.A. Sanderfoot, V. Kovaleva, H. Zheng, and N.V. Raikhel, unpublished data).…”
Section: Are Plant Cells Just Yeast Cells With Chloroplasts?mentioning
confidence: 99%
“…However, the mechanism of recycling of VSR1 from the PVC to the TGN is not yet fully understood. A complex containing the SNAREs SYP41, SYP61, and VTI12 and the Sec1/Munc18-like protein AtVPS45, a potential regulator of vesicle fusion (Dulubova et al, 2002;Bryant and James, 2003), is found at the TGN in Arabidopsis (Arabidopsis thaliana; Bassham and Raikhel, 1998;. SNAREs in the SYP41 complex, along with another SNARE, YKT61/ 62, were found to be sufficient for vesicle fusion in vitro (Chen et al, 2005).…”
mentioning
confidence: 99%